(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The study begins by discussing the history of feminism in English literature, starting from theearly 19th century. It then moves on to discuss the post-freedom era and the changes that occurred in theliterary world during this period. The study also discusses the different types of feminism, including liberalfeminism, radical feminism, and postmodern feminism. One of the main focuses of this study is on therepresentation of women in literature in the post-freedom era. The study examines how women areportrayed in literature and how this representation has changed over time. It analyzes the works ofprominent female writers such as Virginia Woolf, Sylvia Plath, and Toni Morrison and how they havecontributed to the feminist discourse in English literature.